2011
DOI: 10.1017/s204579601100059x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and psychiatrists: what do we know and where to from here?

Abstract: Medicine in most parts of the world is becoming a stressful profession. Psychiatrists represent a high-risk group among doctors for experiencing burnout, alcohol and drug use, posing suicide risk and other forms of work-related stress. There are reports that entrants in the profession of psychiatrists are decreasing globally. Conceptual issues related to burnout are explored and factors contributing to burnout in psychiatrists are reviewed. Methodologically sound studies are needed to help us understand positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 44 publications
2
32
0
5
Order By: Relevance
“…Leiter’s model of burnout posits that DP develops in response to high levels of EE; thus defining DP as a coping mechanism (Leiter, 1991). While some restraint from emotionally engaging with patients may be necessary for sustaining impartiality and objectivity and to protect medical professionals from burnout (Kumar, 2011), maintaining empathy is essential for psychosocial-oncology work given its emotional focus. Therefore, DP is unlikely to be an effective coping strategy for psychosocial oncologists, and is perhaps a less relevant measure of work-related coping in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Leiter’s model of burnout posits that DP develops in response to high levels of EE; thus defining DP as a coping mechanism (Leiter, 1991). While some restraint from emotionally engaging with patients may be necessary for sustaining impartiality and objectivity and to protect medical professionals from burnout (Kumar, 2011), maintaining empathy is essential for psychosocial-oncology work given its emotional focus. Therefore, DP is unlikely to be an effective coping strategy for psychosocial oncologists, and is perhaps a less relevant measure of work-related coping in this population.…”
Section: Discussionmentioning
confidence: 99%
“…professional burnout) are discussed. Finally, while acknowledging that many advances have been made in our comprehension of the factors that are associated with stress and burnout in psychiatrists, Kumar (2011) highlights the need to gain a greater understanding of the determinants of positive work environments and the factors that protect psychiatrists against work stress, calling for a proper examination of the parameters that help psychiatrists find enjoyment or a sense of purpose in their work.…”
mentioning
confidence: 99%
“…Per questo motivo Kumar (2011) nel secondo editoriale focalizza la propria attenzione sulle caratteristiche dello stress lavorativo e del burnout negli psichiatri. L'articolo passa in primo luogo in rassegna le possibili ragioni che rendono tale professione così stressante, ponendo particolare enfasi, ovviamente, ai fattori di stress occupazionali.…”
unclassified
“…In addition, psychiatrists are subjected to high levels of stress and are more prone to present a psychiatric condition such as abuse of alcohol, and/or drugs, and suicide (Bressi et al, 2009;Kumar, 2011). It is not known whether psychiatrists in Brazil are affected in the same way or not: only one study has revealed that a specifi c group of psychiatric residents suffered higher levels of job burden and stress than other healthcare professionals in this analysed group (Zuardi et al, 2011) .…”
Section: Working In Psychiatrymentioning
confidence: 99%